PENERAPAN METODE BAYES DALAM MENGESTIMASI PREMI RISIKO PADA ASURANSI PENYAKIT KRITIS - AGUSTINI, SISILIA MARTINA UTAMI; WIDANA, I NYOMAN; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 9 No 4 (2020)DO - 10.24843/MTK.2020.v09.i04.p305, 2020)
The high number of critical illness cases and the rising medical cost affect the number of insurance claimed. It can be a problem for the insurance company in estimating future claim trend to decide the risk premium cost, so that we need a method to solve the problem which is called Empirical Bayes Credibility Theory (EBCT). Based on that information, the goal of this research is estimating the risk premium cost for critical illness cases using EBCT method. In this research, a large simulation of the expected claim data of critical illness policyholders is used, which are grouped by age and gender. In processing data by applying the EBCT method, the credibility factor is determined first, then the size of the risk premium can be estimated, with the calculation results obtained by a different estimate of the risk premium for each age group based on gender.